(untitled) (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Corona virus disease 2019(COVID-19) is an infectious disease caused by newly discovered coronavirus SARS CoV-2 (Severe acute respiratory syndrome coronavirus 2). Majority of the COVID-19 infections have mild symptoms in general populations but symptoms may be more severe in immunocompromised and elderly patients and may be in CML populations also. We expected most of CML patients in elderly age group may develop severe symptoms of COVID-19 and its severity may vary in different phases of the CML and different types of TKI being used. Method: From January 2020 to June 2021 all adult CML patients receiving treatment from Patan Hospital, identified with SARS Cov-2 infection were included in the study. Those patients who had final outcome from COVID-19 infection was taken. Result: The prevalence of SARS CoV-2 infection in CML population in our hospital is 2.60%. The COVID-19 infection was seen more on female population and younger age group less then 60 years old. Even though the infection rate was higher in the younger age group and infection rate was lesser in CML-CP group, mortality was higher in elderly and advances age group which was statically significant. Regardless of their symptoms, stages, severity of the symptoms, different TKI being used about 92% have fully recovered from COVID-19 infection. Conclusion: About 92% of CML patients had fully recovered from COVID-19 infection. In our study advanced stage and elderly age group were associated with more severity of the disease and higher mortality rate.